2022
DOI: 10.1088/1755-1315/1060/1/012129
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tillage Depth and Lateral Distance of Shallow Plows on the Mean Weight Diameter and the Energy of Soil Fragmentation by Using Locally Manufactured Subsoiler Plow

Abstract: The field experiments were carried out in Basrah province, to study the effect of the distance between the shallow plows (0.40, 0.50, 0.60m), and adding wings on the foot of the subsoiler plow, at tillage depth (0.30, 0.40, 0.50, 0.60m) on the Mean Weight Diameter (MWD) and equivalent energy of the soil fragmentation in clay soil. The results showed that the increase in the plowing depth to 0.60m by the subsoiler without wings on the foot and shallow plows gave largest of the MWD (102.28mm). While the increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Further, it was observed that the relationships between the aggregates larger than 0.25 mm, the mean weight diameter, and the geometric mean diameter were gradually strengthened as the soil layers steadily increased in Figure 3. Several studies showed that they were influenced by different treatments and soil layers, for example, the geometric mean diameter increased with the soil layer depth (Chen et al, 2019; Song et al, 2022), and the value of the mean weight diameter increased as the cultivation depth changed from 30 to 60 cm (Alfaris & Almaliki, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Further, it was observed that the relationships between the aggregates larger than 0.25 mm, the mean weight diameter, and the geometric mean diameter were gradually strengthened as the soil layers steadily increased in Figure 3. Several studies showed that they were influenced by different treatments and soil layers, for example, the geometric mean diameter increased with the soil layer depth (Chen et al, 2019; Song et al, 2022), and the value of the mean weight diameter increased as the cultivation depth changed from 30 to 60 cm (Alfaris & Almaliki, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Alfaris Murtadha A. A. studied the effects of lateral spacing between deep plowing and shallow plowing on the average weight diameter and soil crushing energy of deep plowing by a self-made deep plowing plow [15]. A.…”
Section: Introductionmentioning
confidence: 99%